The central domain of Rhizobium leguminosarum DctD functions independently to activate transcription. - Huala, E (1992)
Sigma 54-dependent transcriptional activators such as Escherichia coli NtrC, Rhizobium meliloti NifA, and Rhizobium leguminosarum DctD share similar central and carboxy-terminal domains but differ in the structure and function of their amino-terminal domains. We have deleted the amino-terminal and carboxy-terminal domains of R. leguminosarum DctD and have demonstrated that the central domain of DctD, like that of NifA, is transcriptionally competent.